Drug utilization pattern in Schizophrenia - Munjely, Elza Joy; R., Bindu Latha Nair; Punnoose, Varghese P. (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Pharmacotherapy is the mainstay of treatment in schizophrenia. The economic impact of this illness is wide ranging, long lasting and huge. The emergence of newer antipsychotics has changed the prescribing pattern. Purpose of this study is to determine the prescription pattern of antipsychotic drugs and to analyse the drug utilization in patients with schizophrenia based on WHO prescribing indicators. Methods: A descriptive study was conducted for a period of 1-year duration at inpatient Department of Psychiatry of a Government Medical College in Kerala, India among 230 schizophrenic patients. The case sheets of patients meeting inclusion criteria were scrutinised to find out the antipsychotic prescription pattern and drug utilization was analysed using WHO prescribing indicators. Analysis was done using descriptive statistics. Results: Newer antipsychotics (55.2%) were prescribed slightly more in preference to older antipsychotic (44.8%) drugs. Out of the newer drugs prescribed olanzapine (20.9%) was prescribed the most followed by risperidone (18%). Haloperidol (22.9%) was the most frequently prescribed older antipsychotic. Majority (71.3%) of the patients were given more than one antipsychotics during the hospital stay. Trihexyphenidyl (27.9%) was the most frequently co-prescribed drug with antipsychotics. Average number of drugs per encounter was 4.19, 73.4% of the drugs were prescribed in their generic name, 50.4% of the encounters were with an injection prescribed. 44.4%of the drugs were prescribed from the EDL (WHO-19th edition). Average drug cost per encounter was Rs.45.43. Percentage of drug cost spent on injections was 8.44%. Conclusions: Newer antipsychotics were more prescribed for schizophrenia of which olanzapine was the commonest. Newer antipsychotics are preferred because of their propensity to cause less side effects and more efficacy. Study of pattern of drug utilization is useful for measuring the economic impact of drug use among patients thereby facilitating rational prescribing.